Material Exchange, Symbolic Recognition: Weltliteratur as Discourse and Practice in Goethe, Carlyle, and Emerson. (2nd January 2021) - Sommer, Tim
ABSTRACT: Thomas Carlyle's activity as a translator and promoter of German literature in nineteenth-century Britain was among the chief signs the ageing Goethe read as inaugurating 'the epoch of world literature'. American essayist Ralph Waldo Emerson, who became Carlyle's transatlantic friend and ally soon after Goethe's death, shared the impression that their contemporary moment witnessed global contact and exchange on an unprecedented scale. Reconsidering the Goethe–Carlyle–Emerson nexus through the lens of the concrete materiality of their transnational interactions, this essay demonstrates that Weltliteratur to the three of them was something discursive as well as material, textual as well as social, and theoretical as well as practical.